Gaps in the knowledge and skills of Portuguese mothers associated with newborn health care - Alexandrina Maria Ramos Cardoso; Heimar de Fátima Marín (Universidade de São Paulo, 2018)
ABSTRACT Objectives: assess mothers' parenting knowledge and skills associated with the parental competence health promotion and monitoring for newborns and infants aged up to six months and determine the key characteristics of mothers who are better prepared for parenting. Method: cross-sectional study conducted in three health centers belonging to a Local Health Unit in the Northern Region of Portugal. Data was collected using clinical interviews conducted with pregnant women or mothers with a child aged up to six months. The tool used contained 21 child health promotion and monitoring indicators associated with different assessment moments: pregnancy, 1st/2nd week, 1st/2nd month, 3rd/4th month, and 5th/6th month. Results: we assessed the knowledge and skills of 629 women. Learning needs were identified for each of the indicators. The mothers who were better prepared for parenting tended to have a higher level of schooling, resided with the child's father, had other children, had planned pregnancy, and intended to breastfeed. Conclusions: the results showed that knowledge and skills were lacking for each of the periods assessed by this study. First-time single mothers whose pregnancy was unplanned and who did not prepare themselves for parenthood may be considered a vulnerable group.